Compact bifluid hybrid stars: hadronic matter mixed with self-interacting fermionic asymmetric dark matter - Mukhopadhyay, Somnath; Atta, Debasis; Imam, Kouser; Basu, D. N.; Samanta, C. (The European physical journal. C, Particles and fields, 2017)
The masses and radii of non-rotating and rotating configurations of pure hadronic stars mixed with self-interacting fermionic asymmetric dark matter are calculated within the two-fluid formalism of stellar structure equations in general relativity. The Equation of State (EoS) of nuclear matter is obtained from the density dependent M3Y effective nucleon–nucleon interaction. We consider the dark matter particle mass of 1 GeV. The EoS of self-interacting dark matter is taken from two-body repulsive interactions of the scale of strong interactions. We explore the conditions of equal and different rotational frequencies of nuclear matter and dark matter and find that the maximum mass of differentially rotating stars with self-interacting dark matter to be ∼ 1.94 M ⊙ with radius ∼ 10.4 km.